Evaluasi Kebijakan tentang Penyelenggaraan Menara Telekomunikasi terhadap Penyedia Menara Telekomunikasi - Widayanto Widayanto; Leroy Samy Uguy; Maya Puspita Dewi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Along with the growth of cellular phone subscribers in Indonesia, cellular network operators continue to strive to build infrastructure to establish broader service coverage areas, thus, increasing the quality of service. Regional Rules & Regulations in DKI Jakarta are intended to regulate the BTS towers within an area. However, they become a barrier for Telecommunications operators to meet the needs of good networks/signals. Changes in the zoning of telecommunication towers can meet the needs of operators and increase customer satisfaction. This study uses qualitative method analysis with an interview. The results show that policy evaluation regarding the implementation of telecommunication towers has yet to meet the needs of telecommunication tower providers (Tower Providers) and has been shown to cause areas that operator signal networks cannot cover. This situation impacts the satisfaction of particular customers and can threaten the business continuity of the operator. Conclusion of the Policy of the Governor of the Special Capital Region of Jakarta Number 14 of 2014, concerning the Implementation of Telecommunication Towers for Telecommunication Tower Providers, the annexse to the zoning of telecommunication towers needs to be reviewed because it has not been able to meet the needs of telecommunication tower providers and can pose a threat to business continuity.